Response of Eucalyptus camaldulensis and Dalbergia sissoo Fertilizers in Sodic Soil - Singh, S. B.; Srivastav, Anubha; Bhatnagar, S. (Indian Forester, 2005)
A field experiment was conducted in mound plantations of Dalbergia sissoo and Eucalyptus camaldulensis on water logged-sodic site. Experimental site was poor in soil nutrients (N, P and K), experiencing waterlogging for the period of 100 to 150 days in a year. Experiment consisted five treatments viz. (1) control, (2) 50 g urea, (3) 50 g each of urea and single super phosphate, (4) 50 g each of urea, single super phosphate and muriate of potash and (5) 5 g each of urea, single usper phosphate, muriate of potash and 10 g of zinc suilphate per plant in Randomized Block Design with three replications. Species did not respond for application of single super phosphate. Application of urea and muriate of potash in Dalbergia sissoo resulted for insignificant higher survival and heigbht of plants. Eucalyptus camaldulensis showed significantly higher height from one year to three years of fertilizer application but level of resonse declined with the increase of plant age. Effect of fertilizer application for increasing volume index was, however, increasing.